Profiling humoral responses to COVID-19 immunization in Kawasaki disease using SARS-CoV-2 variant protein microarrays - Keskin, Batuhan Birol; Liu, Shih-Feng; Du, Pin-Xian; Tsai, Pei-Shan; Ho, Tzong-Shiann; Su, Wen-Yu; Lin, Pei-Chun; Shih, Hsi-Chang; Weng, Ken-Pen; Yang, Kuender D; Huang, Ying-Hsien; Kuo, Kuang-Che; et al. (Analyst (London), 2023)
Kawasaki disease (KD) is a form of acute systemic vasculitis syndrome that predominantly occurs in children under the age of 5 years. Its etiology has been postulated due to not only genetic factors but also the presence of foreign antigens or infectious agents. To evaluate possible associations between Kawasaki disease (KD) and COVID-19, we investigated humoral responses of KD patients against S-protein variants with SARS-CoV-2 variant protein microarrays. In this study, plasma from a cohort of KD (N = 90) and non-KD control (non-KD) (N = 69) subjects in categories of unvaccinated-uninfected (pre-pandemic), SARS-CoV-2 infected (10-100 days after infection), and 1-dose, 2-dose, and 3-dose BNT162b2 vaccinated (10-100 days after vaccination) was collected. The principal outcomes were non-KD-KD differences for each category in terms of anti-human/anti-His for binding antibodies and neutralizing percentage for surrogate neutralizing antibodies. Binding antibodies against spikes were lower in the KD subjects with 1-dose of BNT162b2, and mean differences were significant for the P.1 S-protein (non-KD-KD, 3401; 95% CI, 289.0 to 6512; P = 0.0252), B.1.617.2 S-protein (non-KD-KD, 4652; 95% CI, 215.8 to 9087; P = 0.0351) and B.1.617.3 S-protein (non-KD-KD, 4874; 95% CI, 31.41 to 9716; P = 0.0477). Neutralizing antibodies against spikes were higher in the KD subjects with 1-dose of BNT162b2, and mean percentage differences were significant for the 1-dose BNT162b2 B.1.617.3 S-protein (non-KD-KD, -22.89%; 95% CI, -45.08 to -0.6965; P = 0.0399), B.1.1.529 S-protein (non-KD-KD, -25.96%; 95% CI, -50.53 to -1.376; P = 0.0333), BA.2.12.1 S-protein (non-KD-KD, -27.83%; 95% CI, -52.55 to -3.115; P = 0.0195), BA.4 S-protein (non-KD-KD, -28.47%; 95% CI, -53.59 to -3.342; P = 0.0184), and BA.5 S-protein (non-KD-KD, -30.42%; 95% CI, -54.98 to -5.869; P = 0.0077). In conclusion, we have found that KD patients have a comparable immunization response to healthy individuals to SARS-CoV-2 infection and COVID-19 immunization.Kawasaki disease (KD) is a form of acute systemic vasculitis syndrome that predominantly occurs in children under the age of 5 years. Its etiology has been postulated due to not only genetic factors but also the presence of foreign antigens or infectious agents. To evaluate possible associations between Kawasaki disease (KD) and COVID-19, we investigated humoral responses of KD patients against S-protein variants with SARS-CoV-2 variant protein microarrays. In this study, plasma from a cohort of KD (N = 90) and non-KD control (non-KD) (N = 69) subjects in categories of unvaccinated-uninfected (pre-pandemic), SARS-CoV-2 infected (10-100 days after infection), and 1-dose, 2-dose, and 3-dose BNT162b2 vaccinated (10-100 days after vaccination) was collected. The principal outcomes were non-KD-KD differences for each category in terms of anti-human/anti-His for binding antibodies and neutralizing percentage for surrogate neutralizing antibodies. Binding antibodies against spikes were lower in the KD subjects with 1-dose of BNT162b2, and mean differences were significant for the P.1 S-protein (non-KD-KD, 3401; 95% CI, 289.0 to 6512; P = 0.0252), B.1.617.2 S-protein (non-KD-KD, 4652; 95% CI, 215.8 to 9087; P = 0.0351) and B.1.617.3 S-protein (non-KD-KD, 4874; 95% CI, 31.41 to 9716; P = 0.0477). Neutralizing antibodies against spikes were higher in the KD subjects with 1-dose of BNT162b2, and mean percentage differences were significant for the 1-dose BNT162b2 B.1.617.3 S-protein (non-KD-KD, -22.89%; 95% CI, -45.08 to -0.6965; P = 0.0399), B.1.1.529 S-protein (non-KD-KD, -25.96%; 95% CI, -50.53 to -1.376; P = 0.0333), BA.2.12.1 S-protein (non-KD-KD, -27.83%; 95% CI, -52.55 to -3.115; P = 0.0195), BA.4 S-protein (non-KD-KD, -28.47%; 95% CI, -53.59 to -3.342; P = 0.0184), and BA.5 S-protein (non-KD-KD, -30.42%; 95% CI, -54.98 to -5.869; P = 0.0077). In conclusion, we have found that KD patients have a comparable immunization response to healthy individuals to SARS-CoV-2 infection and COVID-19 immunization.